2016
DOI: 10.1590/1414-431x20155003
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with caffeic and ferulic acid from Baccharis uncinella C. DC. (Asteraceae) protects against metabolic syndrome in mice

Abstract: Fractionation of the EtOH extract from aerial parts of Baccharis uncinella C. DC. (Asteraceae) led to isolation of caffeic and ferulic acids, which were identified from spectroscopic and spectrometric evidence. These compounds exhibit antioxidant and anti-inflammatory properties and have been shown to be effective in the prevention/treatment of metabolic syndrome. This study investigated whether the combined treatment of caffeic and ferulic acids exhibits a more significant beneficial effect in a mouse model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…However, although sucralose was the sweetener providing the highest concentration (10.86 µg/mg of creatinine), the intake of stevia-sweetened drinks yielded the highest bioavailability in terms of percentage. This metabolite would be responsible, to some extent, for the biological benefits expected from the consumption ofmaqui-citrus beverages, especially because of its properties against metabolic syndrome [ 31 , 32 ]. Besides, the combination of this phenolic compound with caffeic acid (CA) has been reported as a promising therapy against multiple aspects of this syndrome, as well as against liver steatosis as recently defined through an overweight mouse model [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, although sucralose was the sweetener providing the highest concentration (10.86 µg/mg of creatinine), the intake of stevia-sweetened drinks yielded the highest bioavailability in terms of percentage. This metabolite would be responsible, to some extent, for the biological benefits expected from the consumption ofmaqui-citrus beverages, especially because of its properties against metabolic syndrome [ 31 , 32 ]. Besides, the combination of this phenolic compound with caffeic acid (CA) has been reported as a promising therapy against multiple aspects of this syndrome, as well as against liver steatosis as recently defined through an overweight mouse model [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…CA was found able to reduce the levels of endoplasmic reticulum stress markers in the liver after a HFD obese induction [ 72 ]. Besides CA’s ability to revert dyslipidemia by reducing TG and TC, studies have shown that CA was able to revert hepatic steatosis in the long run [ 49 , 73 , 74 , 75 ]. In a recent in vivo study, a 12 week CA supplementation on HFD obese mice revealed that CA was able to reduce body weight and fat accumulation together with readings of improved lipid profile with an increased HDL [ 56 ].…”
Section: Ca Vs Dyslipidemiamentioning
confidence: 99%
“…Caffeic acid was found in high amount compared to other phenolic compounds in Citrus macroptera peel which is a strong antioxidant compound [11]. Caffeic acid also showed hepatic protection and prevented fibrosis in various experimental animal models [12][13][14]. This hepatoprotective activity of caffeic acid is linked to improved antioxidant defense and inflammatory state in liver [11,15].…”
Section: Introductionmentioning
confidence: 97%